Living with Smartwatches and Pedometers: The Intergenerational Gap in Internal and External Contexts - Khakurel, Jayden; Tella, Susanna; Penzenstadler, Birgit; Melkas, Helinä; Porras, Jari (Smart Objects and Technologies for Social Good, 2018)
The purpose of this article is to explore and present the range of commonalities and differences between internal and external contexts that influence elderly and younger users’ intentions to use commercial off-the-shelf (COTS) smartwatches and pedometers as motivational tools for physical activity. Therefore, this article follows the contextual action theory and the usability evaluation approach, in which “testing” and “inquiry” were applied to 21 younger participants and 13 fit, elderly participants who were in either the pre-contemplation, contemplation, action, or maintenance behavior-change stage. The results revealed no differences in internal context between the target groups due to both the effect and the useful-ness of the external context. However, there were distinctions between the younger and elderly participants regarding external context, especially in certain aspects of device usability, such as font size, touchscreen interaction, interaction technique, and applications installed, which were the core factors that affected the use of COTS smartwatches and pedometers by the study groups. In addition, the external and internal contexts had a cause-effect relationship, which significantly influenced the use of COTS smartwatches and pedometers.